ptimal Allocation of Orders in the Online Load Distribution and Load Balancing of Assembly Lines - Nima Rahmani; Amir Najafi (مدیریت مهندسی و رایانش نرم)
Proper assembly line planning is one of the challenges production managers face at the tactical level. Failing to apply a secure way of assembly line balancing can cause various complications and problems for the production system. Using the conventional methods for balancing the assembly line cannot balance the load distribution of orders. Online load balancing algorithms can reduce these complications. Old Bachelor Acceptance - Robin Hood‌ (OBA-RH) approach is an effective way for online load distribution. This study aims to evaluate and select a method of order allocation based on the OBA-RH algorithm. Johnson, Palmer, and the meta-heuristic algorithm of annealing are the three allocation approaches studied in this paper, using the data obtained from the production line of polymer films, Plate Company, Iran. The results of the study indicate that Johnson's algorithm and the OBA-RH algorithm offer the best outcome in minimizing system loads.